MobileLAMP: A low-cost, portable incubation device for isothermal nucleic acid amplification - Mohini Bhupathi; Smitha Hegde; Jennifer C. Molloy; Ganga Chinna Rao Devarapu (PLoS ONE, 2026)
Isothermal amplification-based methods for pathogen DNA or RNA detection offer high sensitivity, rapid detection, and the potential for deployment in remote fields and home testing. Consequently, they are emerging as alternatives to PCR and saw a surge in research activity and deployment for the rapid detection of SARS-CoV-2 during the Covid-19 pandemic. The most common isothermal DNA detection methods rely on minimal reagents for DNA amplification and simple hardware that can maintain isothermal conditions and read-out a fluorescent or colorimetric signal. Many researchers globally are working on improving these components based on diverse end-user needs. In this work, we present MobileLAMP, an open-source, 3D-printed incubation device designed for loop-mediated isothermal amplification (LAMP). Composed of off-the-shelf components, MobileLAMP is easily manufacturable and can be powered via any 5V USB source. The device maintains high thermal stability (standard deviation = 0.2°C) across a functional range typically used for LAMP (55–65°C) while consuming only 365 mA of current. Efficacy was demonstrated through the colorimetric detection of SARS-CoV-2 and Salmonella enterica serovar Typhi within a 60-minute incubation period. With a total component cost of less than $5, MobileLAMP provides a highly accessible platform for decentralised molecular diagnostics, supporting both distributed manufacturing and field-based applications.